Inbound Logistics, Conversion Operations And Outbound Logistics Activities at Kaledo Instant, Palu City - Muh Rezki; Suryadi Hadi; Asngadi; Kadek Agus Dwiwijaya (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to describe and analyze the inbound logistics, conversion operations, and outbound logistics activities of the Kaledo Instan MSME in Palu City. This study uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation to gain a comprehensive understanding of the logistics process and production operations. The results show that inbound logistics activities rely on local raw material supplies through online ordering, direct quality checks, and independent transportation using private vehicles. On the conversion operations side, the production process applies a make-to-order system with stages including preparation, cleaning, boiling, using a pressure cooker, steaming, drying, cooling, and packaging. And on the outbound logistics side, Kaledo Instan implements a direct distribution system without the involvement of third-party logistics actors. The main obstacle faced is limited human resources which impacts production capacity and operational efficiency. This study recommends optimizing production schedules, expanding the distribution network through strategic partnerships, and adding a workforce to increase capacity and operational sustainability.